2003
DOI: 10.1016/s1074-7613(03)00321-2
|View full text |Cite
|
Sign up to set email alerts
|

Negligible Role of Antibodies and C5 in Pregnancy Loss Associated Exclusively with C3-Dependent Mechanisms through Complement Alternative Pathway

Abstract: Factors involved in pregnancy failure due to abnormal fetomaternal tolerance are poorly understood. Here we describe distinct defects in placenta formation and subsequent pregnancy loss solely dependent on the activation of the complement alternative pathway and the effector mechanisms provided by the maternal C3. Surprisingly, this effect is independent of other complement activation pathways and of the effector mechanisms provided by other complement components. These findings provide significant insight int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 37 publications
2
93
0
Order By: Relevance
“…A critical role of complement in reproduction has been experimentally characterized by two recent studies showing the deleterious effect on the fetus of unrestricted or increased complement activation, as seen respectively in pregnant mice after either functional deletion of Crry (8,9) or injection of anti-phospholipid Abs (10). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical role of complement in reproduction has been experimentally characterized by two recent studies showing the deleterious effect on the fetus of unrestricted or increased complement activation, as seen respectively in pregnant mice after either functional deletion of Crry (8,9) or injection of anti-phospholipid Abs (10). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the deletion of mouse complement-related receptor protein (Crry), a complement regulatory protein only expressed in mice and rats, results in fetal damage and interruption of pregnancy at or before day 9 (8). The infertility of the Crry Ϫ/Ϫ mother is the consequence of a complement-mediated attack on the fetus rather than a reproduction-specific function of Crry Ϫ/Ϫ , because the fetuses survive if the Crry Ϫ/Ϫ mother is also deficient in C3 (8,9). Another example that highlights the importance of complement in the pathophysiology of reproduction was provided by a recent study of a mouse model of the anti-phospholipid Abs syndrome in which these Abs produced decidual focal necrosis with C3 deposition and neutrophil infiltration in pregnant mice (10).…”
mentioning
confidence: 99%
“…Recent studies have shown that similar to I/R-induced injury, complement activation is required (27,28). Further studies have identified roles for neutrophils, the anaphylatoxin, C5a, and the alternative complement cascade (38,44) in the expression of anti-PL Ab-associated pathology. Because each of these components is involved in mesenteric I/R (5,6,33,35,45), it is possible that Abs with anti-PL specificities are involved.…”
Section: Figure 6 Human Anti-cl Mab Restores I/r-induced Injury In Cr2mentioning
confidence: 99%
“…Perhaps most compelling is the finding that homozygous Crry deficiency is lethal in utero in mice (26), and the placentae of mice carrying Crry Ϫ/Ϫ fetuses demonstrate C3 deposition. This phenotype is rescued when the Crry Ϫ/Ϫ mice are crossed with either C3 Ϫ/Ϫ mice (26) or fB Ϫ/Ϫ mice (70), but crossing them with C4 Ϫ/Ϫ mice or B cell-deficient mice does not promote survival (70). Thus, spontaneous fetal loss in Crry Ϫ/Ϫ mice is due to activation of the alternative pathway and does not require the classical pathway.…”
Section: Spontaneous Fetal Lossmentioning
confidence: 99%